Role of endoplasmic reticulum stress in light‐induced photoreceptor degeneration in mice. (7th January 2013) - Nakanishi, Tomohiro; Shimazawa, Masamitsu; Sugitani, Sou; Kudo, Takashi; Imai, Shunsuke; Inokuchi, Yuta; Tsuruma, Kazuhiro; Hara, Hideaki
Abstract: Exposure to excessive levels of light induces photoreceptor apoptosis and can be a causative factor in age‐related macular degeneration (AMD). However, the cellular events that mediate this apoptotic response are poorly understood. Here, we investigated the roles of endoplasmic reticulum (ER) stress in light‐induced cell death in the murine retina and murine photoreceptor cells (661W). Excessive light exposure induced retinal dysfunction, photoreceptor degeneration, and apoptosis. Furthermore, the accumulation of polyubiquitinated proteins and the transcriptional expression of ER stress‐related factors, including 78‐kDa glucose‐regulated protein (GRP78)/immunoglobulin‐binding protein (BiP) and C/EBP‐homologous protein (CHOP), were increased in light‐exposed retinas. Light exposure also induced both cell death and up‐regulation of polyubiquitinated proteins, S‐opsin aggregation, bip and chop mRNAs in 661W cells in vitro . Knock‐down of chop mRNA inhibited photoreceptor cell death induced by light exposure. Furthermore, treatment with BiP inducer X (BIX), an ER stress inhibitor, induced bip mRNA and reduced both chop expression and light‐induced photoreceptor cell death. These data indicate that excessive ER stress may induce photoreceptor cell death in light‐exposed retinas via activation of the CHOP‐dependent apoptotic pathway, suggesting that the ER stress may play a pivotal role in light exposure‐induced retinal damage. Abstract : In the present study, excessive visible light exposure induced nitric oxide (NO) production, protein aggregation such as S‐opsin in endoplasmic reticulum (ER), and expressions of bip and C/EBP‐homologous protein (chop) mRNAs in photoreceptors. Knockdown of chop mRNA inhibited photoreceptor cell death induced by light exposure. Our findings suggest that ER stress plays a pivotal role in light‐induced photoreceptor degeneration, and that this effect is mediated by CHOP. Therefore, the modulation of ER stress may be a potential therapeutic strategy for the treatment of retinal degenerative diseases.